Personal Branding Strategy Development of Indra Bekti - Aryatama, Aditya; Rudito, Priyantono (The Indonesian Journal of Business Administration, 2014)
Abstract. Showbiz (entertainment) industry in Indonesia has grown rapidly. The number of television and radio continue to increase majorly. Currently there are 13 television stations nationwide and more than 100 local television stations and 2078 radio broadcasters who spread all over Indonesia. The competitions of presenter or announcer become more intense than before.To survived in the competition, each of presenter or announcer should have personal branding strategy. Currently Indra Bekti as a host and presenter didn’t have personal branding strategy. As a result, Indra Bekti become less popular than before.This Final Project is trying to design personal branding strategy for Indra Bekti based on internal and external analysis. Internal factors analyzed by STP (Segmentation, Targeting, Positioning) strategy and also marketing mix. External factors analyzed by Keller’s brand equity. The result from internal and external factor analysis, there are two root cause problem for Indra Bekti. First is unclear segmentation, targeting and positioning, and the last one is Indra Bekt trapped in high level of competition.The research provide recommendation of personal branding strategy for Indra Bekti by improving setting up new segmentation, targeting and positioning supported by marketing mix, so that Indra Bekti will re-gaining inspiring, trendsetter and dare to.Key Words: personal branding, brand equity, marketing mix